Apremilast in Refractory Behçet’s Syndrome: A Multicenter Observational Study - Vieira, Matheus; Buffier, Solène; Vautier, Mathieu; Le Joncour, Alexandre; Jamilloux, Yvan; Gerfaud-Valentin, Mathieu; Bouillet, Laurence; Lazaro, Estibaliz; Barete, Stéphane; Misery, Laurent; Gobert, Delphine; Goulenok, Tiphaine; et al. (Frontiers in Immunology, 2021)
Objective: Mucocutaneous and joint disorders are the most common manifestations in Behçet’s syndrome (BS) and are frequently clustered in the so-called minor forms of BS. There remains a need for safe and effective treatment for joint lesions in BS. We report the long-term safety and efficacy of apremilast in refractory joint and mucocutaneous manifestations of BS. Methods: French nationwide multicenter study including 50 BS patients with either active joint and/or mucocutaneous manifestations resistant to colchicine and/or DMARDs. Patients received apremilast 30 mg twice a day. Primary efficacy endpoint was the proportion of patients with complete response (CR) of articular symptoms at month 6 (M6), defined as resolution of inflammatory arthralgia and arthritis, with joint count equal to zero. Results: At inclusion, the median tender and swollen joint count was of 4 [2-6] and 2 [1-2], respectively. The proportion of CR in joint disease at M6 was 65% (n = 15/23), and 17% (n = 4/23) were partial responders. CR of oral and genital ulcers and pseudofolliculitis at M6 was 73% (n = 24/33), 94% (n = 16/17) and 71% (n = 10/14), respectively. The median Behçet's syndrome activity score significantly decreased during study period [50 (40-60) vs. 20 (0-40); p <0.0001]. After a median follow-up of 11 [6-13] months, 27 (54%) patients were still on apremilast. Reasons for apremilast withdrawal included adverse events (n = 15, 30%) and treatment failure (n = 8, 16%). Thirty-three (66%) patients experienced adverse events, mostly diarrhea (n = 19, 38%), nausea (n = 17, 34%) and headache (n = 16, 32%). Conclusion: Apremilast seems effective in BS-related articular disease refractory to colchicine and DMARDs. Discontinuation rates were significantly higher than that reported in clinical trials.